Development of a Graphical Interface that can be used for LLC Resonant DC-DC Converter Design - Mehmet KUBİLAY; M. Timur AYDEMİR (Gazi Üniversitesi Fen Bilimleri Dergisi, 2020)
In this paper, the design process of LLC resonant DC-DC converters, which have advantages such as high efficiency, low electromagnetic interference (EMI) and high power density, is presented. An interface which uses the first harmonic approximation (FHA) analysis method to calculate circuit parameters has been designed in MATLAB environment. The interface was optimized to choose the most suitable quality factor (𝑄) and inductance ratio (𝐿𝑛) in order to provide high efficiency. Simulations have been carried out in PLECS software for three different power levels to verify the parameters calculated by the developed interface. Variable frequency control method has been used to regulate the output voltage of the LLC resonant converter. Simulation results show that zero voltage switching (ZVS) is achieved over a wide load range, including low load conditions. Also, efficiencies in these load conditions have been measured and the efficiency graphs are presented. When the graphics are examined, it is observed that the maximum efficiency is between 95% and 97% for the three different output power levels chosen. Thermal modeling method has been used in PLECS in order to make the efficiency calculations to resemble the realistic conditions.